The notary's office in the medieval Western Mediterranean: a research project (Studi di storia medioevale e di diplomatica - Nuova Serie, 2021)
This article presents a research project that studies the figure of the medieval notary and his activity in Western Mediterranean societies. In order to justify the development of this project, the article begins with a state of the the historiography concerning the notarial institution. In this way, the results of the research are included in the context of one of the tendencies of contemporary diplomacy: the history of the notarial institution.The text focuses on the main points of a"ention of the project, which is centred on the urban environment of the Crown of Aragon, within a broad chronological framework in order to analyse the evolution of this institution from its beginnings in the 13th century to its definitive establishment in the 15th century. In this framework, relations are established between the notary in these territories and others that are part of the area of influence of Roman law, delimiting it in the Western Mediterranean (Iberian Peninsula, Italica and the islands of Sardinia, the Balearic Islands and Sicily). The study of the notarial institution is approached from four main areas: writing, institutions, society and economy, in order to obtain a complete vision. It is therefore necessary to study the notaries’ handwriting and writing practices, including the circulation of notarial documents and notarial literature and their conservation. For this purpose, it is necess- ary to investigate notarial activity in a selection of public notaries’ offices in urban areas, and this will be done by analysing a selection of notarial registers. As far as institutions are concerned, the aim is to study notarial activity in a number of current organisations, what notarial practice is like in these offices and what documents are generated. Finally, a study is undertaken of the notary’s involvement in medieval society and economic life, his role as intermediary, as arbiter, as guarantor of public faith and, on occasions, as builder of the memory and identity of cities.
Keywords: Notary; 13th - 15th Centuries; Western Mediterranean; Crown of Aragon